Analisis Pengaruh Gaya Kepemimpinan Transaksional, Budaya Kerja Dan Lingkungan Kerja Fisik Terhadap Kinerja Karyawan Factory Sample Room Di PT. Pan Brothers Tbk Kabupaten Boyolali - Yovani Ririsa Sitanggang; Erna Indriastiningsih; Agung Widiyanto Fajar Sutrisno (Manufaktur: Publikasi Sub Rumpun Ilmu Keteknikan Industri, 2024)
The human resources aspect is the most important thing for companies, especially to achieve organizational goals, because the success or failure of an organization is greatly influenced by human factors as people who carry out the work. One of the targets of human resource management in the organizational management function concerns employee performance issues. Employees at the Sewing Department PT. Pan Brothers Tbk Boyolali has an unstable level of performance, which can affect the achievement of company goals. This research aims to explain the factors that can influence a person's performance, such as leadership style, work culture and physical work environment which can influence employee performance. The sample was obtained using a purposive sampling method, and 47 civil servant respondents were selected as the sample. Meanwhile, the data analysis used in this research includes: data quality testing, classical assumption testing, hypothesis testing and multiple regression analysis. The results of the partial significant test (t statistical test) from the research analysis and discussion show that; transactional leadership style, with a t value of 1,555, this value is smaller than t table 1,669. This explains that the Transactional Leadership variable has no effect on the Employee Performance variable. Work Culture, with a t value of 3,033, this value is greater than t table 1,669. This explains that the Work Culture variable has an influence on the Employee Performance variable. Physical Work Environment, with a t value of 2,467, this value is greater than t table 1,669. This explains that the Physical Work Environment variable has an influence on the Employee Performance variable. Meanwhile, the results of the simultaneous significant test (f test) show that Fcount 5,600 > Ftable 2,751 with a significance value of 0.002. So it can be concluded that the two independent variables, namely Transactional Leadership (X1), Work Culture (X2) and Physical Work Environment (X3) greatly influence the dependent variable, namely Employee Performance (Y) at PT. Pan Brothers, Tbk Boyolali.